Virtual 3D environment as a support stragey to the listening learning in English as a foreing language in the students of english 1 at Uniminuto - Astorquiza Bejarano, Adriana Marcela; Bohorquez Bejarano, Cintia Stefany; Jimenez Benito, Gerson (Corporación Universitaria Minuto de Dios, 2014)
This research gets importance at the moment of thinking about benefits that will be add not only to students but also to teachers, to the University and to the teaching English as a foreign language field. For this reason, in the next paragraphs it will be described the importance of studying this problem for students, teachers and the English teaching field. It makes necessary to study this problem because students of English 1, are students of all programs at “Uniminuto” (Corporacion Univeristaria Minuto de Dios) (except for the students of the English teaching program).
Keywords: Listening; Ambiente virtual; Aprendizaje; Educación; PEDAGOGÍA; MÉTODOS DE ENSEÑANZA; AMBIENTES DIGITALES; INNOVACIONES EDUCATIVAS